The influence of gender, ethnicity and academic performance on Islamic Business course - Mohd Hizam Hanafiah,; Muhammad Nasri-Hussain,; Ahmad Azman Mokhtar, (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2015)
Previous studies show that students’ background is found to affect teaching methods, working goals, business simulation performance and value system. A new study was conducted to evaluate the influence of students’ background on their perception of the importance of the main modules in Islamic Business course at university level. A total of 221 undergraduate students in Universiti Kebangsaan Malaysia (UKM) and Universiti Utara Malaysia (UUM) responded to the questionnaire distributed. Results showed that gender, ethnicity and academic performance influenced students’ perception on the main modules in Islamic Business courses. Furthermore, some further discussions and research implications were also discussed.